2015
DOI: 10.6018/rie.34.1.232981
|View full text |Cite
|
Sign up to set email alerts
|

Language learning strategy use by spanish efl students: the effect of proficiency level, gender, and motivation

Abstract: El uso de estrategias de aprendizaje en estudiantes españoles de inglés como lengua extranjera: el efecto del nivel de competencia, el sexo y la motivación

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
2
3
0
2
Order By: Relevance
“…The study suggested that the students employed metacognition as the most frequently employed strategies to assist their learning. This finding corroborates with that of [13], [14], and [15], which also found that metacognitive strategies became the most frequently-used strategies among students. In learning, students had the awareness to plan, monitor, and evaluate their learning.…”
Section: Discussionsupporting
confidence: 91%
“…The study suggested that the students employed metacognition as the most frequently employed strategies to assist their learning. This finding corroborates with that of [13], [14], and [15], which also found that metacognitive strategies became the most frequently-used strategies among students. In learning, students had the awareness to plan, monitor, and evaluate their learning.…”
Section: Discussionsupporting
confidence: 91%
“…Dichos estudios sobre los distintos ámbitos científicos se muestran significativos para las revistas, al igual que para los http://periodicos.letras.ufmg.br/index.php/textolivre Belo Horizonte, v. 12, n. 3, p. 16-36, set.-dez. 2019-ISSN 1983-3652 DOI: 10.17851/1983 investigadores, puesto que la producción científica, su difusión y el impacto de las publicaciones y de los investigadores que en ellas trabajan se fundamentan en ellos (ELKINS; MAHER; HERBERT; MOSELEY; SHERRINGTON, 2010; FRANCESCHET, 2010), mostrando las tendencias más innovadoras y recientes, y sirviendo de orientación en posteriores estudios de las áreas de investigación (VELASCO et al, 2012;VÁZQUEZ;SARASOLA, 2015). Para la obtención de las unidades de análisis se empleó una ecuación de búsqueda de palabras clave unidas con el operador booleano "AND" en el tema y dentro de la colección principal de la Web of Science (marzo-junio de 2019).…”
Section: Métodounclassified
“…Se puede finalizar indicando que las investigaciones sobre la enseñanza de idiomas en el ámbito universitario están empezando a centrarse en la educación superior, en los propios estudiantes y en las creencias que los docentes puedan tener sobre el alumnado. Los temas HIGHER EDUCATION, tal y como reflejan Durham y Kim (2019), STUDENTS, como los estudios realizados por Hafner (2015) y Beliefs, orientados a investigaciones como las de Risueño et al (2016), pueden ser consideradas las bases de investigación de los próximos años dentro de este campo de estudio.…”
Section: Discusión Y Conclusionesunclassified
“…The fact that the average performance of participants in listening was slightly lower than in reading suggests, firstly, the need for students' training on listening strategies. Studies show that the teaching of learning strategies has a positive effect on the development of language learning competences (Risueño Martínez et al, 2015). Secondly, the number of listening exercises to which the students are exposed, could be increased both in the virtual work and in the classroom.…”
Section: Resultsmentioning
confidence: 99%